Representasi Bentuk Penyelesaian Konflik Pernikahan Dini pada Drama Korea: - Augustin, Sava Amalia; Indriastuti, Yudiana (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
18 Again is a Korean drama series that explores the phenomenon of early marriage and pregnancy out of wedlock. Various problems and individual efforts in overcoming conflicts depicted in the drama 18 Again are presented realistically and added a touch of fantasy to support the storyline and the goals of the drama. The phenomenon described is about a person's dreams and wishes if he could return to his youth to make his dreams come true. The storyline is made without leaving the main topic in this drama, namely the problems caused by early marriage and the efforts made by each individual in solving existing conflicts. Even though he is played with two different identities, the characterization in this drama still refers to one character, namely Hong Dae Young. This study uses a qualitative method with John Fiske's semiotic analysis which uses 3 levels of coding, namely the level of reality, the level of representation, and the level of ideology. The conflict management strategy of the Thomas and Kilmann method is also used as a reference and reference for researchers to analyze what and how are the forms of early marriage conflict resolution in the Korean drama 18 Again. After conducting the analysis, the researcher found that there is a form of conflict resolution in early married life which is represented in the Korean drama 18 Again, namely the existence of self-awareness from each individual about the conflict that occurs, then the individual resolves the conflict with related parties in a win-win manner without injuring or detrimental to any party. The existence of a form of conflict resolution that is described at the level of reality, the level of representation, and the level of ideology is inseparable from the process of intrapersonal communication, interpersonal communication, and verbal and non-verbal communication. Keywords: representation, conflict, semiotics, drama.